Properties of Poly(Lactic Acid) Filled with Hydrophobic Cellulose/SiO2 Composites - Kittithorn Lertphirun; Kawee Srikulkit (International Journal of Polymer Science)
Hydrophobic cellulose/SiO2 composites were prepared. Resultant hydrophobic cellulose/SiO2 composites were melt mixed with PLA using a twin-screw extruder to obtain 10 wt% masterbatch. Again, 10 wt% masterbatch was melt mixed with virgin PLA, resulting in PLA containing hydrophobic cellulose/SiO2 at various contents (1 wt%, 3 wt%, and 5 wt%) using a twin-screw extruder (barrel zone temperature: 150/160/170/180/190°C (die zone)). Injection-molded samples were prepared for mechanical properties evaluation. Results showed that poor mechanical properties found at low percent loadings were associated with a significant depolymerization of masterbatch composition due to twice thermal treatments. Note that 10 wt% masterbatch was subjected to injection molding straight away in a one-step process. Results showed that 10 wt% hydrophobic cellulose/SiO2/PLA composites exhibited mechanical properties equivalent to neat PLA. Importantly, the addition of hydrophobic cellulose/SiO2 at high percent loading could favor landfill degradation of PLA via water absorption ability of cellulose. It was expected that enzymatic hydrolysis of cellulose resulted in the formation of lactic acid and silicic acid which consequently catalyzed the hydrolytic degradation (acid hydrolysis) of PLA. The hydrolytic degradation produced carboxylic acid end group which further accelerated the degradation rate.